System zarządzania jakością a charakter zmian w organizacji - Wierzbic, Arkadiusz (Quality system management and change process characteristics in organization, 2006)
This article refers to the problem of a change process characteristics in organizations that implement or maintain the quality management system EN ISO 9001:2000. The approach of evolution versus revolution is discussed concerning issues of the kaizen and BPR methods and the requirements of the EN ISO 9001:2000 standard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 338-343